2010
DOI: 10.3899/jrheum.091452
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis in a North American Native Population: Longitudinal Followup and Comparison with a White Population

Abstract: Compared to white patients, NAN patients with RA develop disease earlier, are more frequently seropositive, have greater large joint involvement, and greater disease burden, although treatment is more aggressive. These differences are present early and persist throughout the disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 21 publications
4
63
0
Order By: Relevance
“…We have previously demonstrated that the Cree/Ojibway North American Native population, like several other North American Native populations, has a high prevalence of RA and multicase families and a high background frequency of predisposing HLA-DRB1 shared epitope alleles (6,9,20,(22)(23)(24). In the present study, our multiplex analyses of 42 proinflammatory and antiinflammatory cytokines, chemokines, and growth factors indicated that, as a group, the serum cytokine profile of the disease-free first-degree relatives more closely resembled that of the RA patients than did the cytokine profiles of North American Native and Caucasian controls.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the Cree/Ojibway North American Native population, like several other North American Native populations, has a high prevalence of RA and multicase families and a high background frequency of predisposing HLA-DRB1 shared epitope alleles (6,9,20,(22)(23)(24). In the present study, our multiplex analyses of 42 proinflammatory and antiinflammatory cytokines, chemokines, and growth factors indicated that, as a group, the serum cytokine profile of the disease-free first-degree relatives more closely resembled that of the RA patients than did the cytokine profiles of North American Native and Caucasian controls.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate is the first-line therapy indicated for rheumatoid arthritis, and was used by 72 % of patients in a recently reported Canadian cross-sectional study [21]; estimates of rates of use of biologics for rheumatoid arthritis from population-based administrative datasets in Ontario was 23.5 % [22], similar to that in the Netherlands (22 %) [23], or the United States (26 %) [24]. Thus, our findings are counterintuitive given findings of worse arthritis severity in First Nations people [12]. A reassuring trend was the increased use of combination therapies in recent years.…”
Section: Discussionmentioning
confidence: 48%
“…By 2012, approximately 20 % of DMARDs were used in combination, and the majority of patients with claims for biologic therapies concomitantly have claims for at least one DMARD, which improves efficacy and survival of biologic agents. Prior to our study, the only publication discussing therapeutic exposures for DMARDs was for Aboriginal patients with rheumatoid arthritis in Manitoba, who had more DMARD, combination therapy and corticosteroid exposures [12]. As the dataset used in our study does not allow exploration of reasons for our observations at the individual level, we cannot identify specifically what factors influence this perceived under-utilization of evidence-based therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthritis is the most common chronic disease experienced by Indigenous populations in Canada, and population-based studies estimate that the prevalence of many arthritis conditions is at least 1.3-1.6 times more frequent than that of the non-Indigenous population [2] with high rates of disability observed [3] including rates in the 25–44 year age group [4]. A significant rise in the prevalence of arthritis conditions in the general population is anticipated over the next 30 years [5] and given that approximately half of the Indigenous population is currently under the age of 25 years [1], there will be a great increase in need for arthritis care.…”
Section: Introductionmentioning
confidence: 99%